The triple bottom line : - Savitz, Andrew W. (Jossey-Bass, 2014)
The classic guide to sustainability strategy and implementation--updated for today's businesses To ensure business success, companies must embrace sustainable management. Firms need to find the overlap between business interests and the interests of society and the environment before they can secure a lasting competitive edge